Pengaruh Disiplin, Motivasi Kerja, dan Analisis Beban Kerja (ABK) terhadap Kinerja Pegawai (Studi Kasus : KPP Pratama Gresik) - Miftahul Fariz; Pompong Budi Setiadi; Sri Rahayu (Studi Ilmu Manajemen dan Organisasi, 2025)
Purpose: This investigation seeks to ascertain the impact between the variables of discipline, work motivation and workload analysis (ABK) on the performance of KPP Pratama Gresik employees.Research methodology: Three statistical tests are used in this quantitative study: multiple linear regression, reliability testing, and validity testing. Questionnaires were distributed to 50 KPP Pratama Gresik personnel in order to ensure sufficient data representation and statistical power. The questionnaires were distributed online to facilitate efficient data collection and improve response rates, considering the constraints on time and access associated with in-person data collection.Results: Employee performance at KPP Pratama is significantly and positively impacted by work discipline. Workplace motivation has a small but favorable impact on KPP Pratama Gresik employees' performance. Employee performance is significantly and positively impacted by workload. Workplace motivation, work discipline, and workload all (simultaneously) have a big impact on KPP Pratama Gresik employees' performance.Conclusions: The study concludes that: (1) Work discipline affects employee performance, (2) Work motivation does not have a significant impact, and (3) A balanced workload supports employee performance.Limitations: This study only focuses on three variables that affect employee performance, namely work discipline, work motivation, and workload, and this research is limited to KPP Pratama Gresik and researchers also realize that some respondents may provide answers that do not reflect the actual reality. so that researchers had difficultly coming directly to the field in the data search process.Contribution: In order to increase employee performance, KPP Pratama Gresik is required to pay attention to the degree of work discipline, work motivation, and workload given by using this research as a reference for future research of a similar kind.Keywords: Discipline Work, Employee Performance, Motivation Work, Workload How to Cite: Fariz, M., Setiadi, P, B. (2025). Pengaruh Disiplin, Motivasi Kerja, dan Analisis Beban Kerja (ABK) Terhadap Kinerja Pegawai (Studi Kasus : KPP Pratama Gresik). Studi Ilmu Manajemen dan Organisasi, 6(1), 63-74.